2011
DOI: 10.1053/j.gastro.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone Mediates Reciprocal Changes in CB 1 and TRPV1 Receptors in Primary Sensory Neurons in the Chronically Stressed Rat

Abstract: Background & Aims Chronic stress is associated with visceral hyperalgesia in functional gastrointestinal disorders. We investigated whether corticosterone plays a role in chronic psychological stress-induced visceral hyperalgesia. Methods Male rats were subjected to 1-hour water avoidance (WA) stress or subcutaneous corticosterone injection daily for 10 consecutive days in the presence or absence of corticoid receptor antagonist RU-486 and cannabinoid receptor agonist WIN55,212-2. The visceromotor response (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 40 publications
(49 reference statements)
5
89
0
Order By: Relevance
“…45 Moreover, exposure to a variety of challenges may profoundly alter CB1 and CB2 gene expression and mRNA levels. 22,30,40,46,47 Given the potential anti-osteoporotic effects of TRPV1 pharmacological stimulation/desensitization, 22 we treated osteoclasts from TM patients with the TRPV1 agonist resiniferatoxin, which led to an increase in CB2 receptor expression and a dramatic reduction of cathepsin K ( Figure 3). This occurred in the absence of any significant change in TRAP mRNA levels ( Figure 3A).…”
Section: Discussionmentioning
confidence: 99%
“…45 Moreover, exposure to a variety of challenges may profoundly alter CB1 and CB2 gene expression and mRNA levels. 22,30,40,46,47 Given the potential anti-osteoporotic effects of TRPV1 pharmacological stimulation/desensitization, 22 we treated osteoclasts from TM patients with the TRPV1 agonist resiniferatoxin, which led to an increase in CB2 receptor expression and a dramatic reduction of cathepsin K ( Figure 3). This occurred in the absence of any significant change in TRAP mRNA levels ( Figure 3A).…”
Section: Discussionmentioning
confidence: 99%
“…Abdelhamid et al reported the involvement of CRF2 receptors in musculoskeletal hyperalgesia in mice exposed to forced swim stress . Chronic subcutaneous administration of corticosterone to rats produced visceral hyperalgesia, as measured by colorectal distension (Hong et al, 2011). Furthermore, chronic water avoidance induces changes in transient receptor potential receptor TRPV1 and the cannabinoid (CB 1 ) receptor expression in the spinal cord (Hong et al, 2009, Hong et al, 2011 which were attenuated by the glucocorticoid receptor antagonist (RU-486).…”
Section: The Hypothalamic-pituitary-adrenal Axismentioning
confidence: 99%
“…Chronic subcutaneous administration of corticosterone to rats produced visceral hyperalgesia, as measured by colorectal distension (Hong et al, 2011). Furthermore, chronic water avoidance induces changes in transient receptor potential receptor TRPV1 and the cannabinoid (CB 1 ) receptor expression in the spinal cord (Hong et al, 2009, Hong et al, 2011 which were attenuated by the glucocorticoid receptor antagonist (RU-486). The results were consistent with previous work from Fereidoni et al where adrenalectomy diminished forced swim stress-induced hyperalgesia in rats (Fereidoni et al, 2007).…”
Section: The Hypothalamic-pituitary-adrenal Axismentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence for the involvement of GR and MR in the development of pain-like behaviors induced by a repeated stress. Systemic MIFE administration reversed colonic hypersensitivity to colorectal distension in response to either a repeated water avoidance stress or subcutaneous CORT injections, with a potential mechanism of altering cannabinoid receptor (CB) type 1 and transient receptor potential cation channel V1 receptors in the dorsal horn of the spinal cord (Hong et al, 2011). In a similar fashion, MIFE or SPIRO administered to the CeA also prevented repeated water avoidance stress-induced pain-like behaviors (Myers and Greenwood-Van Meerveld, 2012).…”
Section: Receptors In Stress Pathways That Modulate Nociceptionmentioning
confidence: 88%